2022
DOI: 10.3390/tropicalmed7120402
|View full text |Cite
|
Sign up to set email alerts
|

Global Research Trends on Monkeypox Virus: A Bibliometric and Visualized Study

Abstract: Monkeypox is a zoonotic viral disease that has recently emerged as another global infection disease. A double-stranded enveloped deoxyribonucleic acid virus the cause of this disease. Since monkeypox is an evolving field of study with a growing interest in public health, it is crucial to study the scientific trend and research activities. This study provides an essential insight into the research response to scientific trends of monkeypox using the bibliometric analysis technique. A literature search for publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…All the mentioned countries are economically developed. Similar to our findings, previous studies on scientific productivity have shown that economically developed countries are more productive regarding scientific studies (16)(17)(18)(19)(20).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…All the mentioned countries are economically developed. Similar to our findings, previous studies on scientific productivity have shown that economically developed countries are more productive regarding scientific studies (16)(17)(18)(19)(20).…”
Section: Discussionsupporting
confidence: 92%
“…It causes an increasing number of cases, especially in children and immunosuppressants, owing to respiratory tract infections (3,4). Although bibliometric studies, a popular method today, have been conducted for many popular or traditional infectious etiologic agents and viruses (14,(16)(17)(18)(19), our study is the first to evaluate hMPV in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that Mpox was the most neglected branch compared with the other three orthopoxvirus genus, such as variola virus, cowpox virus, and vaccinia virus. However, the latest studies demonstrated that the number of Mpox-related publications on epidemiology data, outbreak surveillance, treatment, prevention, vaccines, and so on is showing a blowout trend [ 4 ]. Nevertheless, the emergence of a large amount of information about Mpox may lead to information overload problems and make it difficult for public or scholars to find reliable sources of information and direction.…”
Section: Dear Editormentioning
confidence: 99%
“…Triple-burden diseases, particularly the concomitant incidence of Mpox, HIV, and STIs in the LGBTQIA2S + community, have not been extensively documented in the literature. Therefore, this study uniquely contributes to this eld [53][54][55]. This study used two tools, namely, PoP (Publish or Perish) for literature collection and Vosviewer to analyze keywords further.…”
Section: Current and Future Research Trends Related To Triple-burden ...mentioning
confidence: 99%
“…The larger the occurrence of keywords, the larger the text and circles and the higher the correlation. Occurrences with shorter distances indicate greater power, whereas longer distances have less power (the distance between nodes represents the strength of the relationship between two nodes) [53,54,56].…”
Section: Current and Future Research Trends Related To Triple-burden ...mentioning
confidence: 99%